Perceived Stress and Short-Form Video Application Addiction: A Moderated Mediation Model - Liu, Yinbo; Ni, Xiaoli; Niu, Gengfeng (Frontiers in Psychology, 2021)
Nowadays, short-form video applications have become more and more popular due to its strong appeal to people, especially among college students. With this trend, the phenomenon of short-form video application addiction (SVA) also become prominent, which is a great risk for individuals’ health and adaptation. Against this background, the present study aimed to examine the association between perceived stress and short-form video application addiction, as well as its mechanism - the mediating role of self-compensation motivation (SCM) and the moderating role of shyness. A total of 896 Chinese college students was recruited to complete a set of questionnaire on PS, SCM, shyness, and short-form video applications. The results showed that PS was positively associated with SVA, and SCM partially mediated this association. In addition, both the direct association between PS and SVA and the indirect effect of SCM were moderated by shyness, which were stronger for individuals with high level of shyness. The results could not only deepen our understanding on the underlying factors of short-form video application addiction, but also provide suggestions for relevant prevention and intervention procedures.